Penentuan status mutu air dengan sistem STORET di Kecamatan Bantar Gebang - Bethy Carolina Matahelumual (Geological Agency, 2007)
Water is needed for human life, animals and plants. It can be used as media of transportation (rivers and sea) and energy resources. In Indonesia, groundwater is used for drinking water. Besides the advantages, water could cause disadvantages such as flooding.Intensive exploitation groundwater will cause negative impact prior to degradation of water quality, and its local water surface. The water qualities depend on the environmental conditions. If ecosystem is maintained in balance, it will create natural aquatic cycle.In 2002, study of the water quality was carried out at Bantar Gebang Sub District. The result compared to the STORET System of Environmental Protection Agency (EPA) shows that bad quality of water was caused by its environmental condition and the recent waste disposal site of Bantar Gebang.